Estimating regime-switching Taylor rules with trend inflation - Efrem Castelnuovo; Luciano Greco; Davide Raggi (Bank of Finland, 2008)
This paper estimates regime-switching monetary policy rules featuring trend inflation using post-WWII US data. We find evidence in favour of regime shifts and time-variation of the inflation target. We also find a drop in the inflation gap persistence when entering the Great Moderation sample. Estimated Taylor rule parameters and regimes are robust across different monetary policy models. We propose an `internal consistency' test to discriminate among our estimated rules. Such a test relies upon a feedback mechanism running from the monetary policy stance to the inflation gap. Our results support the stochastic autoregressive process as the most consistent model for trend inflation, above all when conditioning to the post-1985 subsample.
URN:NBN:fi:bof-20140807272
Keywords: E52; E61; E62; 330; active and passive Taylor rules; trend inflation; inflation gap persistence; Markov-switching models